Evaluating Consumer Preferences and Perceptions of Packaged Drinking Water - Ahsan Abdalkhaliq Taha; Hindreen Abdullah Taher; Mohsen Isari; Tayeb Sadeghifar (Journal of Studies in Civil Engineering, 2024)
The global consumption of bottled water is increasing, particularly in developing countries. This study aims to evaluate the quality of packaged water and examine the level of awareness regarding its consumption among residents of Sulaimani City in the Kurdistan region of Iraq, using a structured questionnaire that covers demographics, water quality perceptions, reasons for preference, and satisfaction or grievances. The results reveal that demographic factors such as age, gender, education, and family size significantly affect perceptions. Younger and older individuals view packaged water as more convenient, while middle-aged respondents are less favorable. Higher education correlates with greater environmental awareness, and larger families find packaged water less practical. Shops, social media, and word of mouth are the primary information sources, with males generally expressing more favorable views. The study emphasizes the need to address demographic-specific concerns and raise awareness about environmental impacts. Policymakers and businesses should develop tailored strategies to enhance consumer satisfaction and promote sustainable consumption.